Earned value management como referencia de evaluación del last planner system : un estudio empírico (2016)
It is commonly accepted that the Last Planner system of production control (LPS) has been helping to make more reliable planning and continuous workflow m construction projects. Many cases found in the literature have exposed this benefits measuring the improvements by the percentage of assignments completed (PPC) as "key metric", but it is seen as a poor way to measure the performance or the improvements given for the LPS; this metric is "clearly a defect rate" (H.G. Ballard, 2000a) that reflects the compliance of the commitments but not a measure of productivity improvement. With this in mind, the Earned Value Management (EVM) can be a reliable benchmarking for evaluating the improvement of the LPS in a quantitative way. This research presents an empiric study applying the E VM and the LPS besides the PPC, as a reliable "key metric" of the performances that the LPS produces in the project as a starting point for further researches.